Enforced Expression of miR-101 Inhibits Prostate Cancer Cell Growth by Modulating the COX-2 Pathway In Vivo - Hao, Yubin (2011)
It is commonly agreed that there is an association of chronic inflammation with tumorigenesis. COX-2, a key regulator of inflammation-producing prostaglandins, promotes cell proliferation and growth; thus, overexpression of COX-2 is often found in tumor tissues. Therefore, a better understanding of the regulatory mechanism(s) of COX-2 could lead to novel targeted cancer therapies. In this study, we investigated the mechanism of microRNA-101 (miR-101)-regulated COX-2 expression and the therapeutic potential of exogenous miR-101 for COX-2-associated cancer. A stably expressing exogenous miR-101 prostate cancer cell line (BPH1(CmiR101)) was generated by using lentiviral transduction as a tool for in vitro and in vivo studies. We found that miR-101 inhibited COX-2 posttranscriptional expression by directly binding to the 3′-untranslated region (3′-UTR) of COX-2 mRNA. The regulatory function of miR-101 was also confirmed by using antisense DNA. As a result, exogenous miR-101 is able to effectively suppress the growth of cultured prostate cancer cells and prostate tumor xenografts. The average tumor weight was significantly lower in the BPH1(CmiR101) group (0.22 g) than the BPH1(Cvec) group (0.46 g). Expression levels of the cell growth regulators, such as cyclin proteins, PCNA (proliferating cell nuclear antigen), EGFR (epidermal growth factor receptor), were also studied. In conclusion, COX-2 is a direct target in miR-101 regulation of posttranscription. Exogenous miR-101 suppresses the proliferation and growth of prostate cancer cells in vitro and in vivo. These data suggest that exogenous miR-101 may provide a new cancer therapy by directly inhibiting COX-2 expression.